Tanshinone ⅡA ameliorates acute lung injury by inhibition of the NLRP3 inflammasome - Chen, Tianyu; Qin, Shaoyun; Dai, Ying (Archives of Biological Sciences, 2019)
Paper description: The Nucleotide-binding oligomerization domain (NOD)-like receptor family protein 3 (NLRP3) inflammasome plays an essential role in acute lung injury (ALI). The protective effect of tanshinone IIA on ALI has been verified in several animal models. Tanshinone IIA significantly ameliorated oleic acid-induced pulmonary histological pathology, edema, impaired gas exchange, increased levels of cytokines in rats, and attenuated increased protein levels of NLRP3, caspase-1 and interleukin-1β in pulmonary tissues. Our results extend the knowledge of the protective effect of tanshinone IIA, a potential new tool for ALI treatment. Abstract: Tanshinone IIA is the phenanthrenequinone derivative extracted from the perennial plant Salvia miltiorrhiza Bunge (red sage). We investigated whether inhibition of the nucleotide-binding oligomerization domain (NOD)-like receptor family protein 3 (NLRP3) inflammasome mediates the protective effect of tanshinone IIA in acute lung injury (ALI) induced in rats by oleic acid (OA) injection. Compared with the control treatment, OA injection induced pulmonary histological impairment, increased the lung wet/dry weight ratio (7.0±1.1 vs 4.3±0.6 ) and CO2 partial pressure (PaCO2) (52±6.4 vs 40±3.6 mmHg), decreased arterial O2 partial pressure (PaO2) (63±8.4 vs 100±3.0 mmHg), and increased tumor necrosis factor α (TNFα) (8.8±2.3 vs 5.2±1.5 pg/mL), monocyte chemoattractant protein-1 (MCP-1) (36.1±4.9 vs 25.2±6.6 pg/mL) and interleukin-1β (IL-1β) (15.9±3.2 vs 4.6±1.3 pg/mL) in the bronchoalveolar lavage (BAL) fluid. Tanshinone IIA provided protection against ALI, observed as a reduction in the lung wet/dry weight ratio and CO2 partial pressure, and increased O2 partial pressure. The cytokine increase was also prevented. Tanshinone IIA attenuated increased protein levels of NLRP3, caspase-1 and IL-1β in pulmonary tissues, suggesting that it ameliorates ALI by preventing NLRP3 inflammasome activation. https://doi.org/10.2298/ABS181207013C Received: December 7, 2018; Revised: January 25, 2019; Accepted: January 26, 2019; Published online: March 18, 2019 How to cite this article: Chen T, Qin S, Dai Y. Tanshinone IIA ameliorates acute lung injury by inhibition of the NLRP3 inflammasome. Arch Biol Sci. 2019;71(2):315-20.